ANALISIS STRATEGI PEMASARAN UMKM KAIN MORI (STUDI KASUS PENGUSAHA UMKM KAIN MORI DI KECAMATAN WARUNGASEM): Indonesia - Hendri Hermawan Adinugraha; M. Kholis Setiawan; Hatma Aura Rahmah; M. Zidnil Faza (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2022)
Micro, small and medium enterprises (MSMEs) in the business world are promising businesses, and are businesses that contribute to the Indonesian economy. With the contribution given by MSMEs, it can certainly reduce the burden of government responsibility as a provider of employment for the community. MSMEs are defined as business entities owned by individuals or business entities in accordance with the criteria established by Law No. 20 of 2008. In this study, the MSMEs studied were engaged in marketing with the type of MSME being industrial textiles in Warungasem District. These SMEs apply the Marketing Mix strategy to their marketing. The research method used is a qualitative research method based on the philosophy of postpositivism. After doing the research, the mori cloth SMEs in Warungasem District applied the 7P Marketing Mix, namely (product, price, promotion, place, people, process, physical dividend). In addition, there are advantages and disadvantages of the applied Marketing Mix. However, Marketing Mix has benefits in analyzing finances, etc.